Interpersonal Communication of Islamic Religious Instructors in Human Resources Improvement on Patumbak District Community - Hendra Syahputra; Zainun Zainun; Syawaludin Nasution (Institut Agama Islam Negeri (IAIN) Curup, 2023)
This paper aims to see how the interpersonal communication of Islamic Religious Instructors in conducting counseling to the people of Patumbak District. Most of the population in Patumbak District is Muslim. However, religious practices are still not in accordance with Islamic law. For example, there are still many Muslim people who cannot read the Koran properly. In addition, Islamic religious instructors are agents of development so that training and education programs in the community must be carried out. In addition, the issue of radicalism and massive terrorism is developing so that the preventive effort that can be done is to provide counseling to the community. In the interpersonal communication of extension workers there are also several communication barriers so that the community does not experience rapid changes in quality. This research is a qualitative research by collecting data in the field through interviews, observation, and documentation. There were ten informants consisting of the sub-district government, Islamic religious instructors, and the community. This research was limited to only four villages. The results showed that interpersonal communication of Islamic religious instructors was carried out by means of verbal communication through direct lectures and non-verbal communication with expressions and intonation. Then, as an effort to improve the quality of human resources, it is carried out by holding training and education to read the Koran, provide reading books, and form taklim assemblies. The communication barriers are in the form of physical, semantic, and psychosocial barriers.